American nation-building : case studies from Reconstruction to Afghanistan - Dougherty, Kevin; Pauly, Robert J., 1967- (McFarland & Company, Inc., Publishers, 2017)
"Nation-building enterprises by the United States and the broader international community have run the gamut of success and failure. Examining the history of America's experience in nation-building, this book describes the mechanisms behind what often appears to be a haphazard enterprise"--